MARKETING ANALYSIS OF SUPPLYING THE PHARMACEUTICAL MARKET WITH DRUGS BASED ON BURCH (ARCTIUM LAPPA L.) - Matushchak , M.; Zakharchuk , O.; Horoshko , O.; Sakhatska , I.; Ezhned , M.; Kostyshyn , L. (Collection of scientific papers «ΛΌГOΣ», 2022)
Burdock is a well-known medicinal plant that has been widely used in folk medicine for thousands of years. Now decoction, infusion, tincture, oil solutions, ointments, phytocreams, dry powder from the roots, fresh and dried leaves and seeds of burdock are widely used for arthritis, rheumatism, psoriasis, wounds, tumors, gouty nodes, to improve the condition of hair and trophism scalp; fighting alopecia and dry seborrhea, showing anti-inflammatory, antispasmodic, multivitamin, tonic, antibacterial, immunostimulating and antifungal effects; improves metabolic processes in the body. Taking into account the sufficient raw material base of large burdock, a wide range of pharmacological action of its substances, and the limited range of drugs based on it on the pharmaceutical market, the expediency of manufacturing original means of different directions of action from raw materials of large burdock, in particular, in the conditions of a pharmacy, was determined.